2014
DOI: 10.3354/esr00627
|View full text |Cite
|
Sign up to set email alerts
|

Where the whales are: using habitat modeling to support changes in shipping regulations within National Marine Sanctuaries in Central California

Abstract: Understanding habitat preferences for endangered species is a high priority for management strategies to ensure minimum conflict between human uses and wildlife conservation. The purpose of this study was to identify oceanographic variables that predict occurrences of humpback whales Megaptera novaeangliae within the Cordell Bank and Gulf of the Farallones National Marine Sanctuaries, California, USA, to assess potential conflict with vessel traffic. We used data collected by Applied California Current Ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 77 publications
4
56
0
Order By: Relevance
“…Haida Gwaii), and thus maximum humpback densities in our study area can reasonably be expected to occur in somewhat deeper water. In California, Dransfield et al (2014) similarly predicted that hump backs had an affinity for the shelf break and occurred at greatest frequencies near the 200 m isobath. As with our model, Dalla Rosa et al (2012) determined that latitude was a significant predictor of humpback densities, and suggested this might occur because the extent of preferred, on-shelf habitat varies greatly by latitude in BC.…”
Section: Discussionmentioning
confidence: 91%
“…Haida Gwaii), and thus maximum humpback densities in our study area can reasonably be expected to occur in somewhat deeper water. In California, Dransfield et al (2014) similarly predicted that hump backs had an affinity for the shelf break and occurred at greatest frequencies near the 200 m isobath. As with our model, Dalla Rosa et al (2012) determined that latitude was a significant predictor of humpback densities, and suggested this might occur because the extent of preferred, on-shelf habitat varies greatly by latitude in BC.…”
Section: Discussionmentioning
confidence: 91%
“…Availability of higher resolution remotely sensed data and ocean model output could improve models for all species and ultimately increase our understanding of fine-scale distribution patterns. This is especially important for species with coastal habitats given their generally higher vulnerability to anthropogenic impacts (e.g., ship strikes [10,25]). …”
Section: Discussionmentioning
confidence: 99%
“…In a recent feasibility study, Becker et al [13] demonstrated the nowcast and forecast capabilities of cetacean habitat models based on remotely sensed and ocean modeled SST data. The results provide a foundation for building more complex cetacean habitat models using ocean modeled predictor variables such as sea surface salinity, mixed layer depth [MLD], and SSH, all shown to be important habitat predictors for cetaceans [1,11,25,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the level of effort that has been devoted to characterizing their marine mammal populations and physical and biological components, the California Current and Bering Sea ecosystems are particularly important areas for such modeling efforts (Moore, 2008;Friday et al, 2013;Redfern et al, 2013;Dransfield et al, 2014;Becker et al, 2016). Continuation of these studies should be encouraged because ample environmental and species distribution data already exist, linkages between species occurrence and their environmental drivers have been explored, and these systems have been extensively modeled.…”
Section: Priority Actions and Exemplar Speciesmentioning
confidence: 99%